DISPLAY PROTEROZOIC TECTONIC-ABYSSAL ACTIVIZATION OF ARIAS OF THE UKRAINIAN BOARD IN THE INFORMATION ON ACCESSORY MINERALS - KADURIN, V.; CHEPIZHKO, O.; KADURIN, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The аssосіаtіоn's accessory minerals, their structure and properties can serve reliable criterion formations of belonging granites. The attempt of the decision of a return task, namely restoration of the basic features of evolution before the allocated areas Ukrainian Board (UB) in epoch early-, middlingproterozoic of epoch tectonics-magmatic of activization (TMA) is undertaken on the basis of interpretation of the information on accessory minerals granites. Study of a nature ТМА Ingulo-Inguleckogo, North-West, and Dnestrovo-Bugskogo areas of the Ukrainian board on the basis of interpretation of the information on accessory minerals. The general course proterozoic ТМА by us can be submitted as influence substance-thermal mantles of flows, which have resulted in development antidromic magmatic and generated blocks UB.